Impacts of COVID-19 on global poverty and food security: What more do we know now? - Laborde Debucquet, David; Martin, Will; Vos, Rob (International Food Policy Research Institute, 2022)
The death toll of the COVID-19 pandemic reached near 6 million by early February 2022, two years into the pandemic. With waves of coronavirus variants still raging and the risk of new variants emerging, the human toll will undoubtedly rise further. The socioeconomic impacts of the pandemic are believed to be vast. Yet we still know very little about the true economic costs and the full impacts on poverty, food security, educational attainment, and other social outcomes, and much less about the potentially lasting effects and setbacks to human development.